Avaliação de impactos ambientais da produção de melão em sistema convencional e conservacionista no sumédio São Francisco - Santos, Tayane de Lima (2015)
The Creative Commons License is a leading producer of yellow melon pole for the Brazilian domestic market. Knowing that agricultural activities impact the environment, this study aims to evaluate the environmental impacts through the evaluation of the life cycle, to produce 1 kg of melon grown in Creative Commons License, under two production systems: conventional and conservation. The data relating to conventional melon production system were obtained in the field, with interviews conducted in the Irrigated Perimeter Salitre (Juazeiro-BA), since the data for the conservation systems were obtained in a experimental unit Embrapa Semi-Arid (Petrolina-PE). We performed a sensitivity analysis considering four scenarios: C1 (transport), C2 (packaging) and C3 (fertilizers) and C4 (combination of C1, C2 and C3). The product system under study covers the production of seeds and melon seedlings, agricultural production of fruits, packaging and transport of melons, and the production and transport of inputs used in these processes. Recipe applied the method in the evaluation of the categories: Climate Change, Soil Acidification, Eutrophication of Freshwater, Marine Eutrophication and Water Scarcity; and the Usetox method to assess toxicity. The results indicated that in the long run, conservationists systems have lower environmental impacts. They are shown even if the evaluated categories are affected by three main processes: transport of fruit, packaging of fruits and fertilizer production. Based on the sensitivity analysis, it is observed that the scenario 4 (combining the replacement of the cartons, the use of a mixed transport and the removal of nitrogen fertilizer use) is the greatest reduction of impacts in all categories evaluated